Effect of different surgical positions on the cerebral venous drainage: a pilot study using healthy volunteers. (10th May 2016) - Yeoh, T. Y.; Tan, A.; Manninen, P.; Chan, V. W. S.; Venkatraghavan, L.
Summary: Excessive neck flexion and rotation in certain surgical positions may cause kinking of the internal jugular vein that obstructs cerebral venous blood flow and results in elevated intracranial pressure. The objective of this study was to measure internal jugular vein flow and identify potential impediments to venous flow in supine, prone, and park bench positions using non‐anaesthetised volunteers. Twenty‐seven volunteers were recruited. Venous flow rate was derived from ultrasound measurements of the vessel cross‐sectional area and flow velocity. Change from supine to prone position produced a significant increase in both jugular vein cross‐sectional areas without affecting venous flows. In the right park bench position, the right internal jugular vein cross‐sectional area decreased from 1.2 to 0.9 cm 2 (p = 0.027) without substantive changes in mean venous flow rate (p = 0.91) when compared with supine. In summary, the internal jugular vein flow was not compromised by either prone or park bench positions in non‐anaesthetised volunteers, and careful positioning may prevent kinking of the jugular vein. Further studies in anaesthetised and ventilated patients are needed to validate these results for clinical practice.